Graphene quantum dots modified with adenine for efficient two-photon bioimaging and white light-activated antibacteria - Luo, Zhimin (2020)
A simple two-step microwave-assisted method was developed for the preparation of adenine-modified graphene quantum dots (A-GQDs) with striking fluorescence properties. The prepared A-GQDs with the lateral size of 3–5 nm and single- to few-layer thickness exhibit intense fluorescence with a quantum yield of 21.63% (excited at 350 nm) and an average lifetime of 4.47 ns. The A-GQDs are biocompatible and present two-photon green fluorescence, which render them suitable for two-photon fluorescent cell imaging. More interestingly, we demonstrate for the first time that the A-GQDs also possess white light-activated antibacterial property. Due to their excellent photoluminescence performance and ease of biological conjugation, A-GQDs can be envisioned as an emerging role for many multifunctional biomedical applications.